Galar - a large multi-label video capsule endoscopy dataset - Floch, Maxime Le; Wolf, Fabian; McIntyre, Lucian; Weinert, Christoph; Palm, Albrecht; Volk, Konrad; Herzog, Paul; Kirk, Sophie Helene; Steinhäuser, Jonas L.; Stopp, Catrein; Geissler, Mark Enrik; Herzog, Moritz; et al. (Scientific data, 2025)
Video capsule endoscopy (VCE) is an important technology with many advantages (non-invasive, representation of small bowel), but faces many limitations as well (time-consuming analysis, short battery lifetime, and poor image quality). Artificial intelligence (AI) holds potential to address every one of these challenges, however the progression of machine learning methods is limited by the avaibility of extensive data. We propose Galar, the most comprehensive dataset of VCE to date. Galar consists of 80 videos, culminating in 3,513,539 annotated frames covering functional, anatomical, and pathological aspects and introducing a selection of 29 distinct labels. The multisystem and multicenter VCE data from two centers in Saxony (Germany), was annotated framewise and cross-validated by five annotators. The vast scope of annotation and size of Galar make the dataset a valuable resource for the use of AI models in VCE, thereby facilitating research in diagnostic methods, patient care workflow, and the development of predictive analytics in the field.
Gesehen am 03.11.2025